The a to Z from the Great War to the Great Depression - Wynn, Neil A. (Rowman & Littlefield Publishers, 2009)
This volume examines significant individuals and developments in American political, economic, social, and cultural history between the years 1913 and 1933. It was a time of momentous change including involvement in World War I, the Red Scare, the Jazz Age, the Crash of 1929, and the onset of the Great Depression. It covers the presidencies of Woodrow Wilson, Warren G. Harding, Calvin Coolidge, and Herbert Hoover and the shift from reformism to conservatism. Prohibition and gangsterism symbolized the apparent failure of politics. The A to Z from the Great War to the Great Depression covers this important period in American history with a chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on everything from automobiles, chemicals, and electrical goods, to mass entertainment and the rise of Hollywood, radio, and sport.